2010
DOI: 10.1177/0018720810368674
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human-Automation Consensus in Multiple Unmanned Vehicle Scheduling

Abstract: Objective: This study examined the impact of increasing automation replanning rates on operator performance and workload when supervising a decentralized network of heterogeneous unmanned vehicles. Background: Futuristic unmanned vehicles systems will invert the operator-to-vehicle ratio so that one operator can control multiple dissimilar vehicles, connected through a decentralized network. Significant human-automation collaboration will be needed due to automation brittleness, but such collaboration could ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 20 publications
3
62
1
Order By: Relevance
“…For the 120 second initial replan prompting interval, however, only 8 operators never changed the prompting in- terval. These results reflect a finding from the previous experiment [10], where operators generally could not wait the full 120 seconds between replans. For operators who did use the Replan Interval Dial, the average number of Replan Interval Dial changes was evaluated.…”
Section: Replan Interval Dial Strategysupporting
confidence: 87%
See 4 more Smart Citations
“…For the 120 second initial replan prompting interval, however, only 8 operators never changed the prompting in- terval. These results reflect a finding from the previous experiment [10], where operators generally could not wait the full 120 seconds between replans. For operators who did use the Replan Interval Dial, the average number of Replan Interval Dial changes was evaluated.…”
Section: Replan Interval Dial Strategysupporting
confidence: 87%
“…Surveys conducted after each trial revealed that approximately 35% of the participants were frustrated by the automated planner. Results from this experiment also showed that operators who collaborated with the automated planner had significantly higher performance and lower workload than those who ignored automation requests for replan consideration [10].…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations